Deterioration of Biomass Productivity of a Rangeland Area in the White Nile State, Sudan. (Journal of Faculty of Education, 2021)
Biomass productivity and carrying capacity were determined at three sites in a rangeland area in the White Nile Statem Sudan . A total of 126 quadrates (1× 1m ) wrer used white intervals of 16.5m in between . Seven replicates were used to determine biomass (gm) at each quadrate . The results of biomass and carrying capacity showed that there was a decline in the carrying capacity from 26 a.u./km2/year to only 2.6 a.u./km2/year . The total biomass of the study area was 33540.5 kg/km2. Deterioration in biomass productivity was attributed to drought spells and grazing pressure.
Keywords: White Nile State; Sudan